PERAN STAKEHOLDER MELALUI PENGELOLAAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU SEKOLAH DI SD NO. 2 TUMBAK BAYUH - Chindytia Chindytia; Ida Bagus Gede Surya Abadi; I Made Suardinata; I Kadek Dharma Jaya; I Putu Restya Mandala Diputra (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the role of stakeholders through human resource management in improving school quality at SD No. 2 Tumbak Bayuh. It focuses on the planning, implementation, and evaluation of human resource management, as well as stakeholder involvement in improving school quality. This study employed a descriptive mixed-method approach. Data were collected through semi-structured interviews, SWOT-based observations, and questionnaires distributed to 10 teachers and educational staff. Qualitative data were analyzed through reduction, display, and conclusion drawing, while quantitative data used descriptive statistics (mean, median, mode, and standard deviation). The findings show that human resource management has been implemented based on the school’s vision and mission and supported by leadership and internal programs. Observation results indicate a good category (score 88), while questionnaire results show a mean of 89.5, also categorized as good. However, challenges remain, including limited professional development, inconsistent evaluation follow-up, and suboptimal stakeholder involvement. This study highlights the integration of stakeholder roles in human resource management, providing a comprehensive qualitative and quantitative perspective on improving school quality.